A novel A121T mutation in human cationic trypsinogen associated with hereditary pancreatitis: functional data indicating a loss-of-function mutation influencing the R122 trypsin cleavage site. Issue 8 (29th May 2008) - Felderbauer, P; Schnekenburger, J; Lebert, R; Bulut, K; Parry, M; Meister, T; Schick, V; Schmitz, F; Domschke, W; Schmidt, W E
Abstract : Background: The understanding of genetic risk factors for chronic pancreatitis increased in the last decade with the discovery of mutations in the cationic trypsinogen gene ( PRSS1 ). The first mutation was detected at the R122 autocleavage site of the protein (R122H) and subsequently two other mutations in this region, R122C and V123M, were described that resulted in a similar phenotype of hereditary pancreatitis. This study reports a novel A121T mutation within this region and characterises the resulting molecular properties at the autocleavage site. Methods: Blood samples of a PRSS1 A121T carrier family were analysed for PRSS1 mutations using melting point curve analysis, restriction endonucleases and DNA sequencing. Conformation dependent properties of the mutated sequence were analysed by molecular modelling. The autodegradation kinetic of the mutated trypsin sequence was measured by a novel fluorescence resonance energy transfer (FRET) assay using designed 11 amino acid peptides from PRSS1 aa 118 – aa 127 containing the trypsin cleavage site at aa 122 coupled to a Dabcyl/EDANS FRET system. The kinetic of tryptic peptide cleavage was measured in a fluorescence enzyme linked immunosorbent assay (ELISA) reader. Results: DNA sequencing revealed a novel G to A transition at position 133279 of the published genomic sequence (#U66061 GenBank). The mutation results in an amino acid substitution of alanine by threonine at position 121 (A121T) of the cationic trypsinogen. Four additional mutation carriers could be identified among the relatives while only the first patient developed chronic pancreatitis. Molecular modelling of PRSS1 A121T revealed a change in the bond pattern between the R122 region and the calcium binding loop, whereas FRET assays showed an increased trypsin cleavage rate with a reaction kinetic elevated by more than 80%. Conclusion: The novel PRSS1 A121T mutation highlights the surface exposed region PRSS1 A121-R122-V123 as a hotspot for hereditary pancreatitis associated trypsinogen mutations. Molecular modelling and FRET assays provide evidence for an A121T mutation dependent increase in susceptibility to trypsin digestion at the R122 cleavage site suggesting an enhanced autodegradation and a loss-of-function at the autocleavage site.